Identification of active denitrifiers in full‐scale nutrient removal wastewater treatment systems. (22nd October 2014) - McIlroy, Simon Jon; Starnawska, Anna; Starnawski, Piotr; Saunders, Aaron Marc; Nierychlo, Marta; Nielsen, Per Halkjær; Nielsen, Jeppe Lund
Summary: Denitrification is essential to the removal of nitrogen from wastewater during treatment, yet an understanding of the diversity of the active denitrifying bacteria responsible in full‐scale wastewater treatment plants (WWTPs) is lacking. In this study, stable‐isotope probing (SIP) was applied in combination with microautoradiography (MAR)‐fluorescence in situ hybridization (FISH) to identify previously unrecognized active denitrifying phylotypes in a full‐scale WWTP with biological N and P removal. Acknowledging that different denitrifiers will have specific carbon source preferences, a fully 13 C‐labelled complex substrate was used for SIP incubations, under nitrite‐reducing conditions, in order to maximize the capture of the potentially metabolically diverse denitrifiers likely present. Members of the R hodoferax, D echloromonas, S ulfuritalea, H aliangium and T hermomonas were represented in the 16S rRNA gene clone libraries from DNA enriched in 13 C, with FISH probes optimized here for their in situ characterization. FISH and MAR confirmed that they were all active denitrifiers in the community. The combined approach of SIP and MAR‐FISH represents an excellent approach for identifying and characterizing an un‐described diversity of active denitrifiers in full‐scale systems.